Penerapan Sistem ERP dalam Membuat Project Feasibility, Project Status dan Project Monitoring pada Perusahaan di Bidang Kontraktor - Alianto, Hendra; Wijaya, Santo Fernandi (Bina Nusantara University, 2013)
ERP (enterprise resource planning) is an integrated information system to support the core business activities of an organization. ERP system will help the business unit related to data and information sharing, cost reduction, and improvement of business processes, which will result in an increase in the work (productivity) to become more efficient and effective. However, practically some organizations have problems on running ERP system, some even fail. Therefore, a strategy is needed to help the information systems project. Making project feasibility, project status and project monitoring ERP system can be used as a guide in the design of the ERP program applications to become more user friendly and suitable for the organization needs. The ERP system applied to a contracting company will increase productivity and achieve the level of effectiveness and efficiency of the company's operations. Through strategies in making project feasibility, and status monitoring with ERP system will provide a positive contribution to the development and objectives of the company, so as to improve the effectiveness and efficiency in the processing operations.